Light-dependent modulation of Shab channels via phosphoinositide depletion in Drosophila photoreceptors. - Krause, Y.; Krause, S.; Huang, J.; Liu, C.H.; Hardie, R.C.; Weckström, M. (Neuron, 2008)
The Drosophila phototransduction cascade transforms light into depolarizations that are further shaped by activation of voltage-dependent K+ (Kv) channels. In whole-cell recordings of isolated photoreceptors, we show that light selectively modulated the delayed rectifier (Shab) current. Shab currents were increased by light with similar kinetics to the light-induced current itself (latency approximately 20 ms), recovering to control values with a t(1/2) of approximately 60 s in darkness. Genetic disruption of PLCbeta4, responsible for light-induced PIP(2) hydrolysis, abolished this light-dependent modulation. In mutants of CDP-diaclyglycerol synthase (cds(1)), required for PIP(2) resynthesis, the modulation became irreversible, but exogenously applied PIP(2) restored reversibility. The modulation was accurately and reversibly mimicked by application of PIP(2) to heterologously expressed Shab channels in excised inside-out patches. The results indicate a functionally implemented mechanism of Kv channel modulation by PIP(2) in photoreceptors, which enables light-dependent regulation of signal processing by direct coupling to the phototransduction cascade.